The Art of Expression: Evaluating Speaking Skills Among MTs Riydah El-Ilmi's Eighth Graders - Kholid, M. Fikri Nugraha; Salsabila, Indana; Aryanika, Septa (Cipta Pustaka Nusantara, 2025)
This study provides a descriptive qualitative analysis of the English speaking performance challenges encountered by eighth-grade students at MTs Riyadh El Ilmi. Utilizing a multi-method approach, data were gathered through observation, semi-structured interviews, and video documentation. Student speaking proficiency was evaluated across five key components: grammar, vocabulary, pronunciation, fluency, and comprehension, using a standardized rubric. To ensure data credibility, a dual-rater approach and interrater validation were employed for assessing speaking performances and interview responses, respectively. Findings indicate prevalent issues such as limited vocabulary, mispronunciations, grammatical errors, and disfluency among students. Interview data further revealed significant contributing factors, including inhibition, lack of ideas, low participation, and reliance on the mother tongue. These insights align with existing literature on EFL learning challenges, highlighting the need for pedagogical strategies that address both linguistic deficiencies and affective barriers to enhance students' communicative competence